The Tochi-Gomal Cultural Phase at Rehman Dheri in the Gomal Plain, Dera Ismail Khan: Fresh Evidence - Dr. Saira Naseem; Prof. Dr. Zakirullah Jan (Social Science Review Archives, 2025)
Pakistan has a very rich archaeological and cultural history spanning from the Stone to the Iron Ages. So is the region of Dera Ismail Khan and Bannu Basin in the Northwest Pakistan, where rich heritage sites, diverse cultural traditions and archaeological mounds have been well attested by archaeologist. Around the end of the 4th and beginning of the 3rd millennium BC, a local culture of the early Bronze Age appeared simultaneously in these two regions with distinctive social, cultural, economic and religious traits that significantly influenced the subsequent history and cultures of South Asia. The culture can be placed at the end of the Neolithic/Chalcolithic age of South Asia. First identified at Gumla and Hathala, this culture is unearthed later on at Rehman Dheri, Jhandi Babar, Gandi Umar Khan in the Gomal and at Lak Largae, Lewan and Ter Kala Dheri in the Tochi Valley. The traces being found exclusively in these two regions, hence it is called as ‘Tochi- Gomal Phase’. A substantial amount of cultural data of the Tochi-Gomal Cultural Phase has been unearthed at the archaeological site of Rehman Dheri over the years where relatively larger area is exposed from 1976 to 1995. However, fresh probing at the site is conducted in 2015, 2016 and 2017 by the Department of Archaeology, University of Peshawar and the Directorate of Archaeology and Museums, Government of the Khyber Pakhtunkhwa where fresh evidence about the socio- culture aspect of this culture has been obtained. Such evidence in the form of architecture, technology, socio-economic facet of the society, ceramic manufacturing and design/pattern paved the way for the emergence of urbanism in South Asia and the growth of the Indus Civilization.